Real Estate in the DNA Damage Response: Ubiquitin and SUMO Ligases Home in on DNA Double-Strand Breaks - Dantuma, Nico P.; Pfeiffer, Annika (Frontiers in Genetics, 2016)
Ubiquitin and the ubiquitin-like modifier SUMO are intimately connected with the cellular response to various types of DNA damage. A striking feature is the local accumulation of these proteinaceous post-translational modifications in the direct vicinity to DNA double-strand breaks, which plays a critical role in the formation of ionizing radiation-induced foci. The functional significance of these modifications is the coordinated recruitment and removal of proteins involved in DNA damage signaling and repair in a timely manner. The central orchestrators of these processes are the ubiquitin and SUMO ligases that are responsible for accurately tagging a broad array of chromatin and chromatin-associated proteins thereby changing their behavior or destiny. Despite many differences in the mode of action of these enzymes, they share some striking features that are of direct relevance for their function in the DNA damage response. In this review, we outline the molecular mechanisms that are responsible for the recruitment of ubiquitin and SUMO ligases and discuss the importance of chromatin proximity in this process.